Sustainable Quality Transformation In Agro-Industrial Manufacturing: A Six Sigma–Kaizen Model For Thailand’s Crude Palm Oil Sector - Saswattecha Nantakrit Yodpijit; Somjai Wangrakdiskul; Nattaya Charoensuk; Kanyarat Phromphat; Chalita Boonmee (Jurnal Riset Ilmu Teknik, 2025)
This study enhances the process capability and sustainability of Thailand’s crude palm oil (CPO) production through the integration of Six Sigma DMAIC and Kaizen frameworks. Although Thailand ranks as the world’s third-largest palm oil producer, its CPO frequently fails to meet international standards due to excessive Free Fatty Acid (FFA) and moisture content. To address these persistent inefficiencies, a quantitative–descriptive approach was applied to a Krabi Province mill using 30 days of operational data. The DMAIC methodology systematically identified root causes—unstable sterilization temperature, pressing delays, and inadequate vacuum maintenance—while Kaizen interventions reinforced operator discipline and preventive control. Post-intervention analysis revealed a 19% reduction in FFA, a 36% decrease in moisture, and a 53% reduction in defect rate, accompanied by a rise in process capability index (Cp) from 0.78 to 1.24 and an improvement in sigma level from 4.09 to 4.5. Benchmarking confirmed that Thailand’s performance now closely approaches Malaysia’s automation-led systems while surpassing Indonesia in consistency and energy efficiency. The findings demonstrate that sustainable process improvement can be achieved through data-driven analysis and human-centered Kaizen culture, even in semi-automated contexts. This hybrid model supports compliance with RSPO, ISO 22000, and Bio-Circular-Green (BCG) frameworks while reducing operational waste and cost. The originality of this research lies in establishing an empirically validated Six Sigma–Kaizen hybrid applicable to ASEAN agro-industries, bridging the gap between technological advancement and behavioral quality systems toward globally competitive CPO production.